Increased Levels of Serum Glycosylated Hemoglobin are Associated with Depressive Symptoms in a Population with Cancer (≥49 Years): An Antidepressant-Stratified Analysis [Retraction] - Huang Y (Dove Medical Press, 2021)
Huang Y, Xu Y, Liu A. Clin Interv Aging. 2021;16:205–212. The Editor-in-chief and Publisher of Clinical Interventions in Aging wish to retract the published paper. A review by The Irish Longitudinal Study on Ageing (TILDA) investigation team found it was not possible to replicate the numbers reported in the article and raised concerns the authors had inaccurately interpreted the data. Some of these concerns are specified below.